Business model innovation in SMEs: the role of boundaries in the digital era. Issue 1 (2nd January 2021) - Garzella, Stefano; Fiorentino, Raffaele; Caputo, Andrea; Lardo, Alessandra
ABSTRACT: The digital era is radically changing our societies and how firms do business. Innovating the business model has become a fundamental capability to survive competition, particularly for small and medium-sized enterprises (SMEs). This study investigates the digital-era role of boundary management capabilities in the processes of Business Model Innovation (BMI) in SMEs. Structural Equation Modelling is adopted to analyse data from a survey of 250 Italian experts who possess direct research and consulting experience with SMEs. Our findings reveal that digitalisation and firms' boundaries affect BMI in SMEs. Moreover, our results demonstrate how boundary management, specifically its technological and relational aspects, directly impacts BMI and mediates the relationship between boundary size and BMI. The study also offers important theoretical and practical insights, calling on scholars and managers to give more attention to the boundary management of SMEs in order to support BMI.